Zollinger‐Ellison Syndrome: Classical Considerations and Current Controversies. (6th December 2013) - Epelboym, Irene; Mazeh, Haggi
Learning Objectives: Compare the approaches to management of sporadic and MEN‐1 associated Zollinger‐Ellison syndrome variants. Discuss the controversies in surgical and medical management of Zollinger‐Ellison syndrome. Abstract : Zollinger‐Ellison syndrome (ZES) is an endocrinopathy characterized by gastrin‐secreting tumors, responsible for causing the formation of multiple, refractory, and recurrent peptic ulcers in the distal duodenum and proximal jejunum. Two main variants have been described, sporadic and those found in association with parathyroid and pituitary tumors, a genetic disorder known as multiple endocrine neoplasia‐1 (MEN‐1). Biochemical serum evaluation for elevated gastrin, followed by radiological or nuclear localization of the primary lesion, is mandated for establishing diagnosis. The mainstays of treatment include management of hypersecretory state with medical suppression of gastric acid production and surgical resection of primary tumor for the prevention of malignant transformation and metastatic complications. Medical therapy with proton pump inhibitors has virtually eliminated the need for acid‐reducing surgical procedures. Surgical approach to sporadic and MEN‐1‐associated ZES varies based on our understanding of the natural history of the condition and the probability of cure; however, resection to a negative microscopic margin is indicated in both cases. Postoperative surveillance involves measurement of gastrin level, followed by imaging if elevation is detected. Re‐excision of recurrent or resection of metastatic disease is a subject of controversy; however, at the present time aggressive cytoreductive approach is favored. Abstract : Surgery plays a key role in the management of Zollinger‐Ellison syndrome; however, extent of resection, timing of intervention, performance of prophylactic adjunctive procedures, and reoperation for recurrent disease are topics of controversy. Historical considerations as well as evidence‐based recommendations are summarized in this review.